Electro‐Oxidative Extraction of Methanol from Lignin Using a Three‐Dimensional Graphite Anode - Zichun Xiong; Kazuyo Kobayashi; Aki Miyawaki; Shinya Teranishi; Yoshiharu Sawada; Takashi Hibino (ChemElectroChem)
Abstract This paper reports an electrochemical approach that uses lignin as a resource for renewable and sustainable methanol production. The aromatic rings of lignin have methoxy substituents, which can be oxidatively demethylated to methanol by active oxygen produced at the anode. A graphite electrode fabricated in a sponge form provided sufficient reaction space for the lignin feedstock, efficiently generated active oxygen species from water, and considerably suppressed the overoxidation of methanol to carbon dioxide. As a result, the methanol yield reached approximately 70 % at a temperature of 75 °C, atmospheric pressure, and anode potential of +0.57 V. Another advantage of this technique is that hydrogen evolution reaction (HER) occurred at the cathode and the cathode potential was held at approximately −0.5 V during the HER. Therefore, the cell voltage required for lignin electrolysis was 1.1 V or lower, which means that hydrogen as well as methanol was produced under mild conditions.